The overlooked perspective of police trust in the public: measurement and effects on police job behaviors - Mourtgos, Scott M. (Criminal justice policy review, 2020)
The current study examined whether measures of structural gender equality conditioned the effects of defendant gender on incarceration decisions. Using data from the State Court Processing Statistics (SCPS) database, multilevel logistic regression was used to examine the relationship between both case- and county-level variables on incarceration decisions on a sample of defendants sentenced in state courts. Results indicated that women were less likely to be sentenced to prison than men, but there was no gender difference for jail and noncustodial sentences; however, the structural gender equality measures exerted only slight influences over sentencing outcomes.